ENGLISH TEACHING METHODS - Khurramova Mohinur Askar qizi, (TADQIQOTLAR, 2026)
Abstract This  article  explores  various  English  teaching  methods,  highlighting  their principles,  advantages,  and  limitations.  It  provides  an  overview  of  traditional  and modern  approaches,  including  the  Grammar-Translation  Method,  Direct  Method, Audio-Lingual  Method,  Communicative  Language  Teaching  (CLT),  Task-Based Language Teaching (TBLT), and the Natural Approach. Each method is analyzed in terms  of  its  focus-whether  on  grammar,  communication,  repetition,  or  learner engagement-and suitability for different learning contexts. The article emphasizes the importance of adapting methods to learners' needs and integrating multiple approaches to enhance language acquisition effectively.